Partisipasi Kelompok Masyarakat Dalam Pelestarian Kain Tenun Ikat Tradisional Di Desa Rindi, Kecamatan Rindi, Kabupaten Sumba Timur - Kudu, Umbu; Punia, I Nengah; Arjawa, I.G.P.B Suka (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
Â  ABSTRAK This study, entitled Participation of the community in conservation of traditional ikat in the village Rindi, District Rindi, East Sumba district. The purpose of this study was to analyze the level of participation of community groups in the preservation of traditional ikat in the village Rindi, District Rindi, East Sumba, and describes the obstacles encountered in conservation efforts in the traditional ikat Rindi Village, District Rindi, East Sumba district. The research location is in the village of Rindi, District Rindi, East Sumba district. Source data from this study are primary data and secondary data. The informant set by purposive. Interview guides used only contains the central questions only, while questions derivatives will evolve during the interview, with regard to the relationship with the principal statement. The data used in this study comes from observation, interview, and literature study. The data analysis was conducted on data reduction, data presentation, draw conclusions and implement verification. The survey results revealed Participation in terms of sharing information, working good comrade control group that is in the preparation of equipment and materials, the weaving process, promoting the production of weaving. Constraints facing a group consisting of various aspects, namely technical constraints, social constraints, social constraints, constraints of the availability of capital, human resource constraints and constraints in terms of marketing. Kata Kunci : Participation, Conservation, Woven Fabric Cloth